Learning about Language: Preparing pre-service subject teachers for multilingual classroom realities - Schroedler, Tobias; Grommes, Patrick (Language learning in higher education (Berlin, Germany), 2019)
This paper presents and discusses experiences gained in a German teacher education innovation project on competence and skill development in dealing with multilingualism. New seminar structures were developed, which go hand in hand with a reorganisation of the entire teacher education structure in the University of Hamburg. The aim of these reform implementations is to equip all future subject teachers with relevant skills for dealing with multilingualism and the challenges that learners of German as a second language (GSL) experience. In order to achieve this, a compulsory course on the foundations of multilingualism and language sensitive subject teaching was developed and implemented in the M.Ed. programme (Teacher Degree). In this class students learn about societal multilingualism, basics of contrastive theoretical linguistics, language development, strategies and methods for language sensitive subject teaching as well as practical implementation guidance. Based on a theoretical overview outlining the local conditions with regard to multilingualism and the necessity of language sensitive teaching, the contents of the course are described including a critical reasoning on their substance and place in the course. For a better understanding of the competence development and the effectiveness of the newly introduced seminar(s), a thoroughly validated test instrument is employed in a pre-post design to observe the participants’ skill development. The results of this testing procedure show positive tendencies, yet it remains clear that more work needs to be done in the area.